2007
DOI: 10.1515/bc.2007.028
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary selection pressure and family relationships among connexin genes

Abstract: We suggest an extension of connexin orthology relationships across the major vertebrate lineages. We first show that the conserved domains of mammalian connexins (encoding the N-terminus, four transmembrane domains and two extracellular loops) are subjected to a considerably more strict selection pressure than the full-length sequences or the variable domains (the intracellular loop and C-terminal tail). Therefore, the conserved domains are more useful for the study of family relationships over larger evolutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
88
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(92 citation statements)
references
References 55 publications
4
88
0
Order By: Relevance
“…The evolutionary relationship of the connexin gene family of the zebrafish Danio rerio has been recently reported in great detail (Eastman et al 2006;Cruciani and Mikalsen 2007). These studies demonstrated a particular complexity of connexins in the teleost, with ∼37 connexins found instead of ∼21 in human or the mouse genome.…”
Section: Summary and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The evolutionary relationship of the connexin gene family of the zebrafish Danio rerio has been recently reported in great detail (Eastman et al 2006;Cruciani and Mikalsen 2007). These studies demonstrated a particular complexity of connexins in the teleost, with ∼37 connexins found instead of ∼21 in human or the mouse genome.…”
Section: Summary and Discussionmentioning
confidence: 94%
“…The human ortholog of drCx48.5 is Cx46, a gap junction gene expressed in the murine lens (Paul et al 1991;Pal et al 2000). In contrast, orthologs of drCx39.9 are restricted to fish, amphibian, and birds but cannot be found in mammals (Cruciani and Mikalsen 2007). A single transcript was found for drCx28.6, but the predicted protein of 265 aa is predicted to be encoded by four exons.…”
Section: Cloning Of Seven Novel Connexin Genes Expressed In the Adultmentioning
confidence: 99%
See 2 more Smart Citations
“…Gap junctions in prechordates are composed of innexins (Phelan et al 1998;Phelan 2005). In chordates, connexins arose by convergent evolution (Alexopoulos et al 2004), to expand by gene duplication (Cruciani and Mikalsen 2007) into a 21-member gene family. Three innexinrelated proteins, called pannexins, have persisted in vertebrates, although it is not clear if they form intercellular channels (Panchin et al 2000;Bruzzone et al 2003).…”
mentioning
confidence: 99%